Adaptive Management Tools: Concept Notes System - Mercy Corps (Mercy Corps, 2015)
Mercy Corps finds adaptive management is supported by four different but interconnected elements: Culture, People & Skills, Tools & Systems, and Enabling Environment. These elements are discussed in the context of one of Mercy Corps’ complex programmes in pastoral Ethiopia.

Strategy Testing: An innovative approach to monitoring highly flexible aid programs - Ladner, Debra (The Asia Foundation, 2015)
The international development community has increasingly embraced the idea that finding durable solutions to complex development problems requires new ways of working that move beyond industry norms. This paper makes an important contribution to the current debate by outlining an innovative monitoring system called Strategy Testing (ST). This is the third paper in the Working Politically in Practice paper series, launched together with the Australian Department of Foreign Affairs and Trade.

Introduction to SAVI's way of working - State Accountability and Voice Initiative (SAVI) - SAVI (DFID, 2015)
We are piloting a new approach to identifying and supporting our partners. This breaks with convention in many ways in order to improve impact. SAVI Approach Papers summarise key aspects of SAVI’s way of working. They explain what we do, and why – and link to relevant tools and frameworks. Our approach is summarized in...
Keywords: Practice

Navigating by Judgment: Organizational Structure, Autonomy, and Country Context in Delivering Foreign Aid - Honig, Daniel (Harvard University, Graduate School of Arts & Sciences, 2015)
This dissertation examines when initiatives by International Development Organizations (IDOs) are more, and less, successful. The core argument is that allowing field-level agents to drive initiatives – what I call organizational Navigation by Judgment – will often be the most effective way to deliver aid. This inverts what a classical application of the principal agent model – the workhorse of studies of public management and bureaucracy – would predict, with better performance resulting from less control. In the delivery of foreign aid the costs of monitoring to the principal are often overshadowed by the deleterious effects of the monitoring itself. The core of the argument is that development implementation requires soft information, tacit knowledge, and flexibility that are crowded out by tight controls or an organizational navigation strategy focused on short term measurement and targets. As a result there are increasing returns to Navigation by Judgment in environments that are uncertain or difficult to understand from the outside and tasks where outputs are difficult to observe and/or poorly correlated with long term intervention goals. Insecure political authorizing environments which constrain the autonomy of IDOs prevent these organizations from Navigating by Judgment in situations where this is the best strategy. Empirically, this dissertation examines a cross-IDO dataset of projects (including over 14,000 projects over 50 years over 9 organizations), which I have assembled. It also examines eight cases of development interventions in Liberia and South Africa. These cases are matched pairs comparing the performance and navigation strategies of the US Agency for International Development (a low autonomy IDO) and the UK’s Department for International Development (a higher autonomy IDO) in capacity building and health sector interventions.
Keywords: IMPORTANT

Theory of Change Thinking in Practice - van Es, Marjan; Guijt, Irene; Vogel, Isabel (2015)
Want to know better how your interventions can contribute to change? A Theory of Change (ToC) approach helps in deepening your understanding - and that of your partners - of how you collectively think change happens and what the effect will be of your intervention. Not only does it show what political, social, economic, and/or cultural factors are in play, it also clarifies your assumptions. Once a ToC has been developed, it can be used to continually reflect on it in ways that allow for adaptation and checking of assumptions of your intervention. This user friendly guideline helps you to use a Theory of Change approach. Theories of change are the ideas and beliefs people have – consciously or not – about why and how the world and people change. How people perceive and understand change and the world around them is infused by their underlying beliefs about life, human nature and society. They are deep drivers of people’s behaviour and of the choices they make. Social change processes are complex and characterised by non-linear feedback loops: our own actions interact with those of others and a myriad of influencing factors. This triggers reactions that cannot be foreseen and makes outcomes of change interventions unpredictable. Given these uncertainties, how can we plan strategically and sensibly? How can social change initiatives move forward in emerging change processes in a flexible way, while remaining focused on the goal? In this context of complexity, Hivos has found a theory of change (ToC) approach useful in guiding its strategic thinking and action, as well as its collaborative efforts with others. As it fosters critical questioning of all aspects of change interventions and supports adaptive planning and management in response to diverse and quickly changing contexts. It contributes to the quality and transparency of strategic thinking, and therefore to personal, organisational and social learning. This guide builds on the experiences of Hivos working with a ToC approach. It is a practical guide for Hivos staff in applying a Theory of Change approach, but is also very useful for others working on social change such as social entrepreneurs and innovators. This guide builds on the work of a ToC Learning Group initiated by Hivos and comprising of staff of the Centre for Development Innovation (CDI) of Wageningen University and Research Centre and of experts Iñigo Retolaza Eguren, Isabel Vogel and Irene Guijt. For current thinking and work on the use of Theory of Change thinking in complex change processes, see http://www.theoryofchange.nl